Effects of ACEIs Versus ARBs on Proteinuria or Albuminuria in Primary Hypertension. Issue 39 (September 2015) - Xu, Rui; Sun, Shanmei; Huo, Yan; Yun, Lin; Huang, Shuai; Li, Guohua; Yan, Suhua; Osemene., Inyang
<x xml:space="preserve">Abstract</x> Abstract Although angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) belong to a family of therapies that block the renin–angiotensin system and are suggested to improve proteinuria/albuminuria, it is unclear which is more effective. To compare the effects of ACEIs and ARBs on proteinuria in primary hypertension by performing a meta-analysis covering randomized controlled trials (RCTs). We systematically searched MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials from January 1990 to November 2014. Eligible studies were RCTs of ACEI therapy versus ARB therapy that reported the albumin excretion rate (AER), albumin (Alb), and urinary albumin excretion (UAE) as outcomes. Seventeen RCTs, including 17, 951 patients (without limit of race, age, or sex) with a mean duration of 62.6 weeks, were included. Pooled analysis suggested that ACEIs and ARBs showed no significant differences in AER/Alb/UAE/24-h urine protein/24-h urine total protein in a comparison of 10 trials (SMD 0.09; 95% CI –0.18–0.36; P = 0.52). No significant differences were observed in urinary protein/creatinine ratio (UPCR)/urinary albumin/creatinine ratio (UACR), or albumin/creatinine ratio (ACR) in 7 trials (SMD 0.15; 95% CI –1.88–2.19; P = 0.88). The total outcome of ACEIs and ARBs also showed no significant difference (SMD 0.13; 95% CI –1.03–1.29; P = 0.83). The efficacies of ACEIs and ARBs in controlling blood pressure as a secondary indicator were also similar (SMD –0.50; 95% CI –1.58–0.58; P = 0.37). Based on a meta-analysis of 17 randomized controlled trials including 17, 951 patients, we found that ACEIs and ARBs can reduce urine protein levels, improve blood pressure, and were similarly effective in terms of reducing urinary protein excretion.